Newly found antibodies could lead to treatment against both dengue and zika viruses. (Research'eu results magazine)
Other than both being RNA viruses transmitted by mosquitoes, the dengue and Zika viruses have a few things in common : they both belong to the Flavivirus genus and share similar envelope proteins. Thanks to joint European research, partially funded under the DENFREE project, they can now also be treated with the same antibodies.